The Influence Of Brand Image, Lifestyle, And Product Quality on Purchasing Decisions - Nanda Dwi Iskuntianti; Malia Annissa Faisal; Jumratun Naimah; Vicky F Sanjaya (Profesional Muda Cendekia Publishing, 2020)
This study aims to determine the brand image, lifestyle, and product quality on purchasing decisions for Iphone smartphones. The population used in this study is the consumer iPhone mobile phone users. The method used in this study is a partial test with a Likert scale. The sample in this study were consumers of iPhone smarthphones with a total of 40 respondents. Statistical tests were performed using PLS-based Structural Equation Modeling. The validation test uses the loading factor, convergent validity, and face validity. While the reliability test uses the Cronbach'c alpha value, composite reliability and Average Variance Extracted (AVE). After all the results of the indicator items used in this study are valid and reliable, then the hypothesis is tested. Of the three hypotheses proposed, all of them are supported and for each hypothesis there is one researcher who says the results are not significant. The conclusion of this study is the importance of maintaining brand image for a better lifestyle and maintaining good product quality, in order to get good consumer reviews, besides that it is also important to pay attention to lifestyle in order to remain confident and make purchasing decisions.